2019
DOI: 10.1177/1524838019888885
|View full text |Cite
|
Sign up to set email alerts
|

The Nature and Extent of Qualitative Research Conducted With Children About Their Experiences of Domestic Violence: Findings From a Meta-Synthesis

Abstract: Domestic violence is a significant issue experienced by many children that can have a detrimental impact on their health, development, and well-being. This article reports on the findings of a meta-synthesis that examined the nature and extent of qualitative studies conducted with children about their experience of domestic violence. Studies were identified by a search of electronic databases and included gray literature. Studies were included for review if they were published between 1996 and 2016, were from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 95 publications
(147 reference statements)
0
10
1
1
Order By: Relevance
“…In contrast to hypotheses 1 and 3, as well as to some other studies (e.g. Lucia &Killias, 2011; Noble-Carr et al, 2019; Phillips & Phillips, 2010), but in line with Herrera and McCloskey (2003; for violent behaviour), witnessing physical IPV shows no significant effect within the model that includes violent behaviour, affinity for violence and masculinity norms legitimizing violence as dependent variables in the present study. In these models, delinquent friends (as the independent variable) provided the most important influence.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…In contrast to hypotheses 1 and 3, as well as to some other studies (e.g. Lucia &Killias, 2011; Noble-Carr et al, 2019; Phillips & Phillips, 2010), but in line with Herrera and McCloskey (2003; for violent behaviour), witnessing physical IPV shows no significant effect within the model that includes violent behaviour, affinity for violence and masculinity norms legitimizing violence as dependent variables in the present study. In these models, delinquent friends (as the independent variable) provided the most important influence.…”
Section: Discussioncontrasting
confidence: 77%
“…In addition, Noble-Carr et al (2019) observed a relativizing attitude towards violence when children witnessed IPV at home (e.g. children described domestic and family violence as fights or arguing; see also Karlsson et al, 2016; Ruel et al, 2020).…”
Section: Possible Consequences Of Ipv On Children’s Attitudes Behavio...mentioning
confidence: 99%
“…Systematic reviews are reviews of ‘existing research using explicit, accountable rigorous research methods’ (Gough et al, 2017b , p. 2). Over the past fifteen years, there has been a significant expansion in the conduct and publication of systematic reviews in the field of DVA (MacGregor et al, 2014 ), spanning a wide range of topics from perpetrator programmes (for example, see Bell & Coates, 2022 ) to children’s experiences of domestic abuse (Noble-Carr et al, 2021 ). This body of review level evidence has a critical role to play in developing effective policies and programmes to prevent, reduce and mitigate the effects of DVA across multiple sectors, including public health, criminal justice, and social work (Addis & Snowdon, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, DVA research also offers possibilities for systematic reviewers. The field is growing, underpinned by a rich scholarship on ethical considerations (Bender, 2017 ) and includes a high number of methodological robust qualitative studies, although they tend to be poorly reported (Arai et al, 2021 ; Meyer et al, 2020 ; Noble-Carr et al, 2021 ). A further strength rests with the collaborative and transdisciplinary nature of DVA research, with a significant proportion of studies undertaken and published through non-academic channels, and typically dispersed across disciplines and sectors (Bender, 2017 ; Konya et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aboriginal and Torres Strait Islander women are approximately five times more likely to experience DFV than non-Aboriginal women and 35 times more likely to be hospitalized as a result of being subjected to DFV (Blagg, Williams et al, 2018). DFV can have long-term impacts and increases the risk for mental health issues as well as social, behavioral, and learning difficulties (Campo, 2015; Campo & Tayton, 2015; Clark & Graham-Bermann, 2017; Noble-Carr et al, 2019). In addition, it is estimated that over two thirds of women who have reported experiencing DFV had children in their care at the time of the perpetration of violence (ABS, 2017).…”
mentioning
confidence: 99%